Protein kinase D promotes activity‐dependent AMPA receptor endocytosis in hippocampal neurons. (5th October 2021) - Oueslati Morales, Carlos O.; Ignácz, Attila; Bencsik, Norbert; Sziber, Zsofia; Rátkai, Anikó Erika; Lieb, Wolfgang S.; Eisler, Stephan A.; Szűcs, Attila; Schlett, Katalin; Hausser, Angelika
Abstract: α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) type glutamate receptors (AMPARs) mediate the majority of fast excitatory neurotransmission in the brain. The continuous trafficking of AMPARs into and out of synapses is a core feature of synaptic plasticity, which is considered as the cellular basis of learning and memory. The molecular mechanisms underlying the postsynaptic AMPAR trafficking, however, are still not fully understood. In this work, we demonstrate that the protein kinase D (PKD) family promotes basal and activity‐induced AMPAR endocytosis in primary hippocampal neurons. Pharmacological inhibition of PKD increased synaptic levels of GluA1‐containing AMPARs, slowed down their endocytic trafficking and increased neuronal network activity. By contrast, ectopic expression of constitutive active PKD decreased the synaptic level of AMPARs, while increasing their colocalization with early endosomes. Our results thus establish an important role for PKD in the regulation of postsynaptic AMPAR trafficking during synaptic plasticity. Abstract : Synaptic connections in the brain are continuously weakened or strengthened in response to changes in neuronal activity. This process, known as synaptic plasticity, is the cellular basis for learning and memory. An important aspect is the trafficking of AMPA receptors (AMPARs), the main mediators of fast excitatory transmission in the brain. We show that PKD promotes basal and activity‐dependent AMPAR endocytosis in primary hippocampal cultures and thus plays an important role in postsynaptic AMPAR transport during synaptic plasticity.